An Analysis of Elementary School Prospective Teachers’ Critical Thinking: A Gender Perspective - Saputri, Dwi Yuniasih; Yusuf, Munawir; Subagya, Subagya (Universitas Pendidikan Indonesia, 2023)
This study aspires to analyze the elementary school prospective teachers' critical thinking viewed from the gender aspect. The method employed was a quantitative study with a descriptive approach. Conducted at Elementary School Teacher Education Department, this study involved 25 male students and 25 female students as participants. Data collection was done by means of a test about environmental pollution material. Facione's theory, comprising interpretation, evaluation, analysis, inference, and self-regulation, was used to analyze critical thinking. To analyze the data, descriptive quantitative analysis was employed. The findings shows that female elementary school prospective teacher students have better critical thinking skills than male students. It is shown by the higher average of every indicator in females with 3.1 in the good category, while the males’ average is 2.46 in the fair category. The lecturers have to take gender into account in facilitating critical thinking skills by implementing supportive learning methods, facilitating students’ learning styles, and providing challenging questions.